KNOWLEDGE AND THE ROLE OF CADRES IN THE IMPLEMENTATION OF EARLY DETECTION OF TODDLERS DEVELOPMENT USING KPSP - yani, nuryanin; T.W., Ayesha H.N, Nurwening (UPPM Politeknik Kesehatan Kemenkes Ternate, Maluku Utara, Indonesia, 2017)
Introduction: The development of toddlers is noteworthy considering the population size is large enough. Early detection is an important development with KPSP carried out in an effort to facilitate early detection of developmental disorders that can be given early intervention and referral early in children, in the end the quality of a child's development may be optimal. Trained cadres have the authority to monitor the development of children with KPSP Method: cross sectional analytic approach. Population health cadres in the district Lembeyan with Random sampling techniques with independent variable knowledge and skills of cadres, the role of cadres in the implementation of early detection of early childhood development using KPSP as the dependent variable. Results: Correlation between knowledge and the role of cadres in the implementation of early detection of toddlers development using KPSP analyzed using Spearman Rank test with the results of 0565, while the role and the skills to 0.485 correlation value. Conclusion: there is a relationship of knowledge to the role of cadres and there is a relationship between skill to the role of cadres in the implementation of early detection of toddler development using KPSP. It is hoped the clinic routinely provide refresher material on monitoring developments and increasing the number of screening kit (infrastructure for monitoring developments).